SOCIAL ACCEPTANCE OF PROFITABILITY OF POLISH BANKS IN THE CONTEXT OF INTRODUCTION OF THE BANK TAX - Paweł Mrowiec (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
In the opinion of general public Polish commercial banks earn too much from their activities as compared to the contributions they pay to the state budget. The banking sector is a very important part of the Polish economy and the dynamics of assets belonging to financial institutions within the last 25 years were from two to three times igher than the dynamics of Polish GDP1 . Thus, development of the financial sector especially in the pre-crisis period was considerably faster than development of the real sphere. Tax regulations in force used to be very favourable for the banking sector. Financial services were exempted from VAT. However, as of 1 February 2016 a new tax commonly referred to as bank tax, was introduced. The rate of the tax was set on the level of 0.44% of a bank’s assets value. Introduction of this tax on one hand aroused many controversies and fears with respect to potential consequences for the stability of the financial sector but on the other, related opinion polls showed a great deal of public approval. This is a completely new argument in the discussion over advantages and disadvantages of the new tax. The author of the paper argues that introduction of a tax which enjoys public support will contribute to the increase in public trust in financial sector. The aim of the paper is to present social acceptance of profits generated by the Polish banking sector in the context of public needs whose satisfaction relies on the efficiency of the state budget. The research methods applied by the author include opinion surveys and deduction method.